(untitled) (The Pretoria Student Law Review, 2021)
In light of the 2009 United Nations Copenhagen climate change conference, South Africa announced that in order to combat climate change it would commit to reducing domestic greenhouse gas (GHG) emissions by 34 per cent by 2020 and 42 per cent by 2025. Due to this commitment, a carbon tax will be implemented as from 1 January 2015. This market-based instrument has received broad attention sparking debate as industries most affected, namely Eskom and the petroleum sector, have rallied together in complaint. The main debate being that despite the politically ambitious commitment to reduce GHG emissions, little scientific, economic or comparative evidence has been given to show that an influence will actually be had on the amount of GHG emitted. The purpose of this article is not to provide a detailed analysis of the entire scope of the South African climate change policy. It focuses on the more limited issue of carbon taxation. This does not however mean that the numerous other competing policy options, which still beg for attention, are not viable or will not be implemented in the future.